PREVALENCE, ANTIMICROBIAL SUSCEPTIBILITY PATTERN AND RISK FACTORS OF MRSA ISOLATED FROM CLINICAL SPECIMENS AMONG MILITARY PATIENTS AT 48 MEDICAL COMPOUND IN SANA’A CITY-YEMEN - Ali Al-Safani, Ahmed Mohammed; Al-Shamahy, Hassan A.; Al-Moyed, Khaled A. (Universal Journal of Pharmaceutical Research, 2018)
Objective: Methicillin-resistant strains of S. aureus evolved in the 1970 and have troubled hospitals worldwide with persistent infections in patients. The objectives of this study were to determine the prevalence, antimicrobial susceptibility pattern and risk factors of MRSA isolated from clinical specimens among military patients at 48 Medical Compound in Sana’a city - Yemen. Methods: The study included 233 patients of whom suffering from Staphylococcus aureus infections. Specimens and data collected from November 2016 to November 2017. Standard methods of isolation and identifications were used to isolate bacteria in pours culture then Staphylococcus aureus were identifying using standard cultural techniques. MRSA was determined by the disc diffusion method to oxacillin and antimicrobial susceptibility testing was performed by the disc diffusion method for selected antibiotics. Results: The prevalence rate of MRSA was 19.3% and there was significant association between MRSA and older age patients, and surgical site infections. There was higher rate of antibiotics resistant for tested antibiotics in MRSA isolates comparing with lower rate of antibiotics resistant in MSSA. 60% of the MRSA isolates were resistant to vancomycin. They were also susceptible to erythromycin and rifampicin (100%), but showed resistance to Cotrimoxazole and Gentamycine. Conclusion: In conclusion, the emergence of S. aureus isolates resistant to vancomycin and other wide range of antibiotics have raised MRSA in Yemen into a multi-drug-resistant ‘Superbug”, making it more and more dangerous than ever in hospital environments. Regular surveillance of hospital associated infections and monitoring antibiotic sensitivity pattern and strict drug policy for antibiotics used within and outside the hospital environments are recommend. Peer Review History: Received 22 March 2018; Revised 6 May; Accepted 11 June; Available online 15 July 2018 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewer(s) detail: Dr. Tanveer Ahmed Khan , Hajvery University, Lahore, Pakistan, tanveerahmedkhan754@gmail.com Dr. Wilman Ismael Carrillo Terán , Technical University of Ambato Avda, Ecuador, wilmanct@gmail.com